Enhance radio resource allocation techniques for fractional frequency reuse base station in mobile wimax cellular network - Mohammed Khalid Salman Fadhil (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2014)
Broadband wireless connections have emerged as a solution to satisfy users' demands for modern E-application, such as LTE and WiMAX. According to Ericsson's official anticipations, the global mobile broadband subscriptions will reach 6.5 billion at the end of 2018. This orientation of the public toward the wireless broadband internet services needs more attention in terms of adequate resources and bandwidth to meet users' demands for modern E-services. WiMAX, for instance, is a promising technology to deliver a high speed broadband internet connection for fixed and mobile users. The IEEE 802.16e is a mobile version of WiMAX technology; it can be used in cellular network deployment.